Gradient Boosting Decision Tree Classification-Based FacialEmotion ‎Detection Using Machine Learning - Rajeswari, Ms. K.; Tharaneedharan, S. (International Journal of Basic and Applied Sciences, 2025)
Facial Emotion Detection is an automated task of computer vision used to determine the emotion of the human face based on facial ‎expressions in still images or video. It is done by extracting the facial features and labeling them as happy, sad, angry, or surprised. It finds ‎universal application in human-computer interaction, mental condition examination, and surveillance mechanisms. Achieving high levels of ‎accuracy in detecting Facial Emotion in systems using different types of lighting and occlusions is quite a challenge that current systems fail ‎to achieve. They also have the problem of generalizing due to different facial constructions, age groups, and cultural expressions. To solve ‎those problemsContrast Limited Adaptive Histogram Equalization (CLAHE) is used to pre-process facial expressions in images or videos. ‎This improves the local contrast and reveals subtle emotional guidance by boosting brightness in small areas and restricting noise expansion. ‎Further, Elephant Herding optimization (EHO) is used to optimize the learning process, find all similar features of the face, and select the ‎most essential features in the case of feedback facial recognition. The Gradient Boosting Decision Tree (GBDT), with its effective input in ‎the non-linear relation and amelioration in the accuracy of the prediction, was used in carrying out the classification task. The performance ‎indicators are used to evaluate the model, including accuracy89.3%, precision87.2%, recall86.5%, specificity88.1%, AUC-ROC of 0.91, and ‎Matthews Correlation Coefficient (MCC) of 0.84. Experimental findings indicate that the designed approach reaches the peak tenth in the ratio ‎of the support rate of dominant emotion categories and regularly exceeds the classical schemes in most severe and complicated facial‎recognition contexts, which indicates high reliability and resilience of the regimen in various challenging tasks‎.